Techno-economic and environmental assessment of grid and solar photovoltaic microgrid supply options for isolated off-grid rural communities toward sustainable and affordable electricity in Nkoranza South, Bono East, Ghana - Nicholas Saddari; Nana Sarfo Agyemang Derkyi; Forson Peprah; Samuel Gyamfi; Genevieve Kwarteng Donkor (Results in Engineering)
Ghana has achieved about 86 % of electricity access, yet about five (5) million Ghanaians do not have access to electricity. Isolated off-grid rural communities face a major challenge in assessing clean electricity in Ghana due to the long distance and low number of inhabitants. This study is motivated to technically, economically, and environmentally present a comparative analysis of grid and solar photovoltaic microgrid of electricity supply to rural communities toward sustainable and affordable electricity, using a case study of Nkoranza, Ghana. Two supply options (19.5 km grid extension and 746.1 kWp solar PV microgrid) were evaluated for technical feasibility using geographical information system survey and economic viability using the net present value, internal rate of return, discounted payback period and profitability index. An environmental impact assessment (carbon dioxide emission) of the two supply options was performed using empirical analysis. The findings show a negative net present value of $ 383,017.20 for the grid option, whereas the solar microgrid option had a positive net present value of $431,882.12. The grid expansion option had internal rate of return, discounted payback period and profitability index of 2 %, infinity years, and 0.6, respectively. In the same vein, the solar microgrid option had 24 %, 7 years, and 1.6, respectively. The carbon dioxide savings due to the solar microgrid stood at 31,248,254.2 tons ($253,110.86 in monetary value) in 25 years. The study shows that constructing a solar photovoltaic microgrid to serve the community's electricity need is more lucrative than grid extension for the same purpose.